THE USE OF BOOK CREATOR TO BOOST STUDENTS’ MOTIVATION IN WRITING: A CASE STUDY - Adibah, Almas (Bajang Institute, 2024)
Students have different level of motivation in learning English as there have always been a number of obstacles they find during the process. When it comes to writing, most students even lose their interest because it is difficult in many ways for EFL learners. To boost their motivation to write, Book Creator is used. The Book Creator is a web-based tool that enables students to create creative and inspiring digital books. Besides inserting texts, it allows students to add pictures and audios thus their digital book will be richer and more exciting to read. They can choose either download it as an e-book or publish it online on the website. By using Book Creator, students enjoy the class and have more motivation to write as they are given a channel not only to put their ideas into writings but also explore their creativity to make a product. Their motivation to write before and after using the Book Creator is observed by Academic Writing Motivation Questionnaire (AWMQ) by Payne. Students also have to fill out a questionnaire to find out their perception towards the use of the Book Creator in writing class.